MEMBANGUN LOYALITAS PELANGGAN KLINIK KECANTIKAN MYRII JAMBI: ANALISIS STRATEGI COST LEADERSHIP DENGAN KEPUASAN SEBAGAI MEDIATOR - Fajri, Irham; Dahmiri; Indrawijaya, Sigit (Journal of Business Studies and Management Review, 2025)
The primary objective of the development of beauty clinics is to attract and maintain customer loyalty toward the services offered. This study aims to analyze the effect of cost leadership strategy on customer loyalty at MyRii Beauty Clinic Jambi, both directly and indirectly through customer satisfaction as a mediating variable. In addition, this research examines the effect of cost leadership strategy on customer satisfaction, as well as the effect of customer satisfaction on customer loyalty. This study employs a quantitative approach and is classified as explanatory research. The sampling technique used was purposive sampling, with the sample size determined using the Slovin formula, resulting in 359 respondents. The findings indicate that cost leadership strategy have a positive effect on customer loyalty at MyRii Beauty Clinic Jambi. Affordable and efficient pricing are able to enhance customer satisfaction, which in turn encourages customer loyalty. Furthermore, customer satisfaction is proven to play a crucial role in strengthening the relationship between cost leadership strategy with customer loyalty, both through direct effects and as a partial mediating variable. These findings confirm that customer satisfaction is a key factor in building sustainable customer loyalty.